PENGARUH LAMA PENDIDIKAN, STATUS EKONOMI DAN SOSIAL BUDAYA TERHADAP USIA KAWIN PERTAMA DI KABUPATEN MUARO JAMBI TAHUN 2015. - Pantun Bukit (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
The age of first marriage was determined to the health condition of women. BKKBN Jambi showed the new regulations about marriage, that the woman can marry as minimal as about 21st years old.  Those consideration taken by identified the woman’s health condition according to the physical and mental. Muaro Jambi has occupied the third high of marriage as many as 16.542 couples for last two years. Sungai gelam and Jambi Luar Kota were the highest of marriage in Muaro Jambi Regency. BKKBN (2015) said that many factors could be influence the age of first marriage, three of them are the long education, economy status, and cultural. Early survey showed that early break of school caused the marriage happen. It was carry as the economy status. Their parents  thought that after their daughter married, all of her necessary is her husband’s responsibility. Therefore the cultural also support it. They lived in the environtment which people that consider close relation was bad thing before marriage. This research used path analysis that aim to find out the influence of long education, economy status, and cultural to the age of first marriage year 2015. It began on September, 10th 2015 till November ,15th 2015. The research instruments was used quesioners and interview. The population as many as 858 respondent and the sample as many as 214 respondents. The descriptive result of this research showed that about7% respondents has long education as long as >12 years, 24% respondents 10-12 years, 25% respondents 1-6 years, 44% respondents 7-9 years. The salary of them about 32% respondentshas salary as much as ≤ Rp. 849.000, 47% respondents Rp. 850.000 – Rp. 1.690.000 , 15% respondents Rp. 1.700.000 – Rp. 2.549.000, 6% respondents ≥ Rp. 2.550.000.The cultures of respondents was less of good. The ages of the respondents show that by 214 respondents 4 of them was 14 years old, 14 was 15 years old, 63 was 16 years old, 27 was 17 years old, 27 was 18 years old, 24 was 19 years old, 17 was 20 years old, 11 was 21 years old, 19 was 22 years old, 4 was 23 years old, 3 was 24 years old dan 1 orang 25 years old. All of the variables influence the age of the first marriage as many as 71.4%. The long education influence the age of marriages as many as 33,91%, economy status was 23,63% and cultural was 13,98%. It was the problem that could be fixed by cooperation between organitations such as health government, education government, in regency till subdistrick of Sungai Gelam and Jambi Luar Kota. Keyword: Educational, economic, social and cultural status